The ethics of ESG: Sustainable finance and the emergence of the market as an ethical subject - Archer, Matthew (Focaal, 2022)
Sustainable finance is generally understood as the integration of environmental, social, and governance (ESG) considerations into the investment process. Based on participant observation of sustainable finance and impact investing conferences between 2015 and 2020, and a series of interviews with the sustainability team and several portfolio managers at a large European bank in 2018 and 2019, I show how the compulsion to define and measure sustainability indicators reflects the emergence of the market itself as an ethical subject, one that is capable of making the most efficient, and thus the most ethical, decisions. This has implications for ethical intersubjectivity in sustainability more broadly. I situate this claim alongside recent work in anthropology and geography on the translation of social and environmental values into financial values, as well as on work in the anthropology of ethics and its intersection with the anthropology of finance.